Weight control and cancer preventive mechanisms: role of IGF-1-mediated signaling pathways - Xie, Linglin; Wang, Weiqun (My University, 2013)
Overweight and obese not only increase the risk of cardiovascular disease and type-2 diabetes mellitus, but are also now known risk factors for a variety of cancers . Weight control, via dietary calorie restriction (DCR) and/or exercise, has been demonstrated to be beneficial for cancer prevention in various experimental models, but the underlying mechanisms are still not well defined. Recent studies conducted in a mouse skin carcinogenesis model show that weight loss induced a significant reduction of the circulating levels of IGF-1 and other hormones, including insulin and leptin, resulting in reduced IGF-1-dependent signaling pathways, i.e., Ras-MAP-proliferation and Akt-PI3K-antiapoptosis. Selective targeting IGF-1 to Akt/mTOR and AMPK pathways, via negative energy balance, might inactivate cell cycle progression and ultimately suppress tumor development. This review highlights the current studies focused on the major role of reducing IGF-1-activated signaling via weight control as a potential cancer preventive mechanism.
Keywords: Weight control; Dietary calorie restriction; Exercise; Cancer prevention; IGF-1 signaling